In vitro and in silico evaluation of Centaurea saligna (K.Koch) Wagenitz-An endemic folk medicinal plant - EMRE, GİZEM (ELSEVIER SCI LTD, 2018)
Centaurea saligna (K.Koch) Wagenitz is an endemic plant used in Turkish folk medicine as antibacterial, tonic, astringent, choleretic, anti-rheumatic, diuretic, and antipyretic. This study attempts for the first time to assess the possible enzyme inhibitory potential, antioxidant activity, and determine the phytochemical profile of the ethyl acetate, methanol, and water extracts of C. saligna. The water extract had the highest phenolic content (30.18 mg GAE/g extract) and the most potent oxidant scavenging activity ((120.53, 111.90, 68.43, and 157.88 mg TEN extract, for CUPRAC [cupric reducing antioxidant capacity], FRAP [ferric reducing antioxidant power], DPPH [2,2-dipheny1-1-picrylhydrazyl], and ABTS [2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid] assays respectively)). The water extract (4.16 mg KAE/g extract) also inhibited tyrosinase and contained high level of catechin (214 mu g/g extract). Ethyl acetate extract showed potent inhibitory capacity against cholinesterases (2.22 and 2.21 mg GALAE/g extract for acetyl and butyryl cholinesterase, respectively) and alpha-glucosidase (23.80 mmol ACAE/g extract). High concentration of apigenin (2472 mu/g extract) was identified in the ethyl acetate extract. In silico studies showed that apigenin binds to the enzymatic pocket of alpha-glucosidase and is stabilised by a network of hydrogen bonds and pi-pi stacking. Data collected in the present study advocates the need for further investigation geared towards validation of C. saligna for the management of complications related to the target enzymes, such as diabetes type II, Alzheimer's disease, and epidermal hyperpigmentation. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Centaurea saligna; Folk medicine; Enzyme inhibitors; Bioactive compounds; Antioxidants; TOTAL PHENOLIC CONTENT; ANTIOXIDANT ACTIVITY; ALPHA-GLUCOSIDASE; ETHNOPHARMACOLOGICAL SURVEY; PHYTOCHEMICAL PROFILE; BIOLOGICAL-ACTIVITIES; ALZHEIMERS-DISEASE; TURKEY; ACID; L.